2000
DOI: 10.1007/3-540-46592-8_3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of High-Valent Oxo-Metalloporphyrins

Abstract: High-valent oxo metalloporphyrins have been known as reactive intermediates in the catalytic cycles of many heme enzymes and in the oxidation reactions mediated by synthetic metalloporphyrins. In this review, we survey studies of high-valent oxo metalloporphyrins in the past decade. In Sect. 2, electronic structures and magnetic properties of compound I and compound II species in various heme enzymes are discussed on the basis of recent studies of synthetic model complexes of the compound I and compound II. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 212 publications
0
13
0
Order By: Relevance
“…Excellent reviews on the reactivity of iron-oxo porphyrin complexes can be found in the literature, including those from Fujii (2000, 21 2002 22 , 2016 23 ) Meunier et al (2004), 24 Groves (2006), 25 Newcomb (2006), 26 Nam (2007), 27 Costas (2011), 28 Ray and Meyer (2012), 29 and Rutkowska-Zbik (2014) 30 . Dedicated chapters in The Porphyrin Handbook (2000), 18,31-34 Handbook of Porphyrin Science, 35 and other compilations 36-38 can also be found.…”
Section: Metal-oxo Porphyrinoid Complexes As Models For Biological Oxmentioning
confidence: 99%
“…Excellent reviews on the reactivity of iron-oxo porphyrin complexes can be found in the literature, including those from Fujii (2000, 21 2002 22 , 2016 23 ) Meunier et al (2004), 24 Groves (2006), 25 Newcomb (2006), 26 Nam (2007), 27 Costas (2011), 28 Ray and Meyer (2012), 29 and Rutkowska-Zbik (2014) 30 . Dedicated chapters in The Porphyrin Handbook (2000), 18,31-34 Handbook of Porphyrin Science, 35 and other compilations 36-38 can also be found.…”
Section: Metal-oxo Porphyrinoid Complexes As Models For Biological Oxmentioning
confidence: 99%
“…The chemistry of porphyrin-metal-oxo [10], corrole-metal-oxo [7,[11][12][13][14][15], and corrolazine-metaloxo species [16,17] have received considerable attention. Iron(IV)-oxo porphyrin radical cation models of Compound I have been known for more than two decades [18], and they have been characterized by various spectroscopic methods, such as UV-vis, EPR, Mö ssbauer, EXAFS and Raman spectroscopies [19].…”
Section: Introductionmentioning
confidence: 99%
“…Such species have been trapped in the catalytic cycles of heme enzymes such as cytochrome P450 (2,3) and peroxidases (where these species are referred to as compounds I and II) (1). The generation and characterization of corresponding biomimetic oxo-iron(IV) porphyrin complexes have significantly enhanced our understanding of their structural, spectroscopic, and reactivity properties (4,5). A diiron(IV) intermediate called Q has been identified with Mössbauer spectroscopy in the catalytic cycle of the nonheme diiron enzyme methane monooxygenase (6)(7)(8); this intermediate has been proposed from extended x-ray absorption fine structure (EXAFS) evidence to have an Fe IV 2 ( -O) 2 core structure (9).…”
mentioning
confidence: 99%